Role of Chromodomain-Helicase-DNA-Binding Protein 4 (CHD4) in Breast Cancer - Novillo, Apolonia; Fernández-Santander, Ana; Gaibar, Maria; Galán, Miguel; Romero-Lorca, Alicia; El Abdellaoui-Soussi, Fadoua; Gómez-del Arco, Pablo (Frontiers in Oncology, 2021)
Chromodomain-helicase-DNA-binding protein 4 (CHD4) is an epigenetic regulator identified as an oncogenic element that may provide a novel therapeutic target for the treatment of breast cancer (BC). CHD4—the core component of the nucleosome remodeling and deacetylase (NuRD) complex—may be mutated in patients with this disease. However, information on CHD4 mutants that might allow their use as biomarkers of therapeutic success and prognosis is lacking. The present work examines mutations in CHD4 reported in patients with breast cancer and included in public databases and attempts to identify their roles in its development. The databases revealed 81 point mutations across different types of breast cancer (19 of which also appeared in endometrial, intestinal, nervous system, kidney, and lymphoid organ cancers). 71.6% of the detected mutations were missense mutations, 13.6% were silent, and 6.2% nonsense. Over 50% affected conserved residues of the ATPase motor (ATPase and helicase domains), and domains of unknown function in the C-terminal region. Thirty one mutations were classified in the databases as either ‘deleterious’, ‘probably/possibly damaging’ or as ‘high/medium pathogenic’; another five nonsense and one splice-site variant were predicted to produce potentially harmful truncated proteins. Eight of the 81 mutations were categorized as putative driver mutations and have been found in other cancer types. Some mutations seem to influence ATPase and DNA translocation activities (R1162W), while others may alter protein stability (R877Q/H, R975H) or disrupt DNA binding and protein activity (R572*, X34_splice) suggesting CHD4 function may be affected. In vivo tumorigenecity studies in endometrial cancer have revealed R975H and R1162W as mutations that lead to CHD4 loss-of-function. Our study provides insight into the molecular mechanism whereby CHD4, and some of its mutants could play a role in breast cancer and suggest important implications for the biological comprehension and prognosis of breast cancer, identifying CHD4 as a novel therapeutic target for BC patients.